The Use Of Time Series, Cross Section Model In The Growth And Yield Studies of Indonesia Forests - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRACT Establishing permanent plots in growth and yield studies is the most effective methods in deriving reliable and accurate estimates of growth and yield data. With this method, a complete time series observations can be obtained and the stand dynamics can be drawn as well. On the other hand, permanent ploti establishment is expensive and a time consuming activity that most of the research stations in Indonesia cannot affort it. While the development of forest management both in plantation and mixed, uneven-aged forests is at the moment at the full gear, the need for growth and yield information has to be accomodated. This paper explored the potential use of time series-cross section model in providing sufficiently dependable estimates of growth and yield information in much faster way. Time series-cross section model offers a combination of using larger size of individuals while reducing the series of observations. Hypothetically it can be stated here that, if such model can be constructed and verified, then, at least temporarily, the problem faced by Indonesian forest managers with growth and yield information can be solved.